A conceptual model of nitrogen dynamics for the Great Barrier Reef catchments. (December 2021) - Adame, M.F.; Vilas, M.P.; Franklin, H.; Garzon-Garcia, A.; Hamilton, D.; Ronan, M.; Griffiths, M.
Abstract: Nitrogen (N) from anthropogenic sources has been identified as a major pollutant of the Great Barrier Reef (GBR), Australia. We developed a conceptual framework to synthesise and visualise the fate and transport of N from the catchments to the sea from a literature review. The framework was created to fit managers and policymakers' requirements to reduce N in the GBR catchments. We used this framework to determine the N stocks and transformations (input, sources, and outputs) for ecosystems commonly found in the GBR: rainforests, palustrine wetlands, lakes, rivers (in-stream), mangroves and seagrasses. We included transformations of N such as nitrogen fixation, nitrification, denitrification, mineralisation, anammox, sedimentation, plant uptake, and food web transfers. This model can be applied to other ecosystems to understand the transport and fate of N within and between catchments. Importantly, this approach can guide management actions that attenuate N at different scales and locations within the GBR ecosystems. Finally, when combined with local hydrological modelling, this framework can be used to predict outcomes of management activities.